Ubiquitin E3 Ligase c-Cbl Is a Host Negative Regulator of Nef Protein of HIV-1 - Zhang, Hong-Guang; Guo, Jing; Yuan, Yukang; Zuo, Yibo; Liu, Jin; Zhu, Li; Miao, Ying; Chen, Xiangjie; Jin, Lincong; Huang, Fan; Ren, Tengfei; He, Jiuyi; et al. (Frontiers in Microbiology, 2020)
Nef is an accessory protein encoded by human immunodeficiency virus type-1 (HIV-1) and plays important roles in regulating HIV-1 infection and viral replication. Interestingly, HIV-1 Nef can promote degradation of numerous host proteins to disrupt cellular antiviral immune response. However, how HIV-1 Nef is degraded by host factors remains largely unexplored. Here, we identified c-Cbl as a host ubiquitin E3 ligase of HIV-1 Nef. We found that c-Cbl interacts with Nef and reduces protein levels of HIV-1 Nef but not Gag, Vif or gp120. Further studies demonstrated that c-Cbl promoted Lys48-linked polyubiquitination of HIV-1 Nef, thus attenuating protein stability of HIV-1 Nef. Importantly, cellular c-Cbl ubiquitinated and degraded Nef proteins produced by HIV-1 NL4-3 virions, and ultimately restricted HIV-1 virion production. This study reveals a ubiquitination and proteasome-dependent degradation mechanism of HIV-1 Nef protein, and could provide potential strategies for fighting against HIV-1.